True or false :
If a , b and c follows an arithmetic progression , then ( b + c − a ) , ( c + a − b ) and ( a + b − c ) also follows an arithmetic progression.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given that a , b , c form an arithmetic progression, we know that
d 1 = c − b , d 1 = b − a
Therefore, it satisfies c − b = b − a
Now, given a progression ( b + c − a ) , ( c + a − b ) , ( a + b − c )
If it was an arithmetic progression:
d 2 = ( c + a − b ) − ( b + c − a ) = 2 a − 2 b , d 2 = ( a + b − c ) − ( c + a − b ) = 2 b − 2 c
This gives 2 a − 2 b = 2 b − 2 c ⟹ − 2 ( b − a ) = − 2 ( c − b ) ⟹ b − a = c − b
The second progression also satisfies the same condition, therefore we can say that it is an arithmetic progression too.
Therefore, the answer is True
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Arithmetic Progressions
If a , b , c is in arithmetic progression,
− 2 a , − 2 b , − 2 c is in arithmetic progression,
So, ( a + b + c ) − 2 a , ( a + b + c ) − 2 b , ( a + b + c ) − 2 c is in arithmetic progression,
So, ( b + c − a ) , ( c + a − b ) , ( a + b − c are in arithmetic progression.
So, the answer is True .